(untitled) (Swiss Medical Weekly, 2015)
Six multidisciplinary competence centres (Clinical Trial Units, CTUs) in Basel, Berne, Geneva, Lausanne, St. Gallen and Zurich provide professional support to clinical researchers in the planning, implementation, conduct and evaluation of clinical studies. Through their coordinated network, these units promote high-quality, nationally harmonised and internationally standardised clinical research conduct in Switzerland. We will describe why this network has been established, how it has been successful in stilling the growing need for clinical research support, which training and education opportunities it offers, and how it created national awareness for the still-existing hurdles towards clinical research excellence in Switzerland. Taking the CTU Basel as an example, we show that a considerable number (25%) of the studies submitted for regulatory approval in 2013 were supported by the CTU, decreasing the number of findings in ethics reviews by about one-third. We conclude that these achievements, together with a Swiss national funding model for clinical research, and improved national coordination, will be critical factors to successfully position Swiss clinical research at the international forefront.